Stabilization and solidification of hazardous, radioactive, and mixed wastes - Spence, R. D. 1948-; Shi, Caijun (CRC Press, 2005)
Providing a wealth of information, this in-depth volume covers waste characterization, transport and testing methods as well as including case studies, demonstrations, guidelines and an examination of regulatory considerations.
Keywords: Hazardous wastes -- Stabilization.; Hazardous wastes -- Solidification.; Radioactive waste disposal.; Mixed radioactive wastes.; Radioactive wastes.; Hazardous wastes.; elektronické knihy; electronic books